Revisiting of an Islamic Options Permisibility from Shariah Perspectives - Ahmad Khaliq; Hassanudin Mohd Thas Thaker (Global Review of Islamic Economics and Business, 2014)
The popularity of derivative instruments especially in managing uncertainty (risk)had become popular after several financial crises that occurred since the Great EconomicDepression. There are various tools have been developed in managing risk such as the Options,Forwards, Futures and Swaps. In addition, these kinds of tools are commonly used by institutional and individual investors. Given this popularity, conventional risk management strategies is completely against from Islamic risk management as Islamic financial market arekeep on growing drastically at Cumulative Average Growth Rate (CAGR) of 15% on yearlybasis (Mckinsey, 2005). This is clearly shows that, Islamic finance development are in line withconventional financial development. Therefore, there is need to maintain consistency in productstructures offered by these two financial markets. The complexity is mainly contributed by thestructures and the design of the products especially on Islamic derivatives tools. Therefore, to get a significant picture of the Islamic risk management tools, this paper will only examines thecontemporary derivative instruments namely; Option and the Islamic viewpoints of thisinstrument . As we know, Islamic finance is governed by Shariah principle and guidelines whichprohibit Riba, Gharar, and Masir etc. Therefore, this paper attempts to explore the validity ofoptions from Islamic and Shariah perspectives by reviewing Islamic scholars opinions on anoptions market.